2008
DOI: 10.1007/s00192-008-0616-9
|View full text |Cite
|
Sign up to set email alerts
|

Moderate weight loss in obese women with urinary incontinence: a prospective longitudinal study

Abstract: This study assessed the effect of moderate weight loss in obese women with urodynamically proven urinary incontinence using the International Consultation on Incontinence recommended outcome measures. Sixty-four incontinent women were offered a weight reduction programme with a target loss of 5-10%. This included a low-calorie diet and exercise. An anti-obesity drug (Orlistat) was offered to those who failed to achieve their target. Forty-two (65%) achieved the target weight loss and had significant reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 23 publications
1
37
0
13
Order By: Relevance
“…In this research, the pelvic floor muscle strength, measured by the modified Oxford scale, increased significantly one year after bariatric surgery compared to the preoperative period. Auwad et al found similar results in their study group, patients who achieved weight loss ≥ 5% of body weight showed significant increase in pelvic floor muscle strength measured by the Oxford Scale, along with improvement in urinary leakage 1 . In this study, the quality of the muscle contraction of the pelvic floor through perineometry, as well as in the modified Oxford Scale, showed a significant increase in mean peak contraction of the pelvic floor postoperatively compared to the preoperative period.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this research, the pelvic floor muscle strength, measured by the modified Oxford scale, increased significantly one year after bariatric surgery compared to the preoperative period. Auwad et al found similar results in their study group, patients who achieved weight loss ≥ 5% of body weight showed significant increase in pelvic floor muscle strength measured by the Oxford Scale, along with improvement in urinary leakage 1 . In this study, the quality of the muscle contraction of the pelvic floor through perineometry, as well as in the modified Oxford Scale, showed a significant increase in mean peak contraction of the pelvic floor postoperatively compared to the preoperative period.…”
Section: Discussionsupporting
confidence: 61%
“…In obese, studies show that after massive, surgically induced weight loss, there is resolution or alleviation of the symptoms of urinary incontinence 14,15,20,22,26,27 . Urinary incontinence usually leads to withdrawal from social interaction, psychosocial frustrations and early institutionalization.2 Therefore, its diagnosis and treatment are particularly important in women with morbid obesity, contributing to the improvement of quality of life 1,13,17,20,26,27 . The aim of this study is to analyze the effects of weight loss induced by bariatric surgery on pelvic floor function.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos demonstram que a redução do peso leva a significante diminuição dos episódios de IU, da noctúria, melhora na qualidade de vida e decréscimo da pressão intravesical 11 11,[33][34][35] suportam a perda de peso como opção de tratamento para mulheres com sobrepeso ou obesas e incontinentes, pois a redução dos episó-dios semanais de IU de 50 a 60% com a perda de peso é comparável com a melhora observada em estudos com terapias comportamentais e com terapias farmacológi-cas 35 . Porém, Kudish et al 7 observaram que a redução de peso não parece estar associada à regressão significativa do prolapso de órgãos pélvicos, sugerindo que o dano no assoalho pélvico, relacionado ao ganho de peso, pode demorar mais tempo para regredir ou ser irreversível.…”
Section: Discussionunclassified
“…Recentemente, a identificação do excesso de peso e da obesidade é sugerida como parte integrante dos programas de reabilitação do AP 8 . Assim, a redução de peso tem sido incluída no tratamento da incontinência urinária (IU) e do prolapso genital 9,10 , uma vez que a redução de 5% do peso corporal contribui para redução da severidade da IU 11 . Ambas as condições, obesidade e disfunções do AP, impactam negativamente na qualidade de vida das mulheres que as apresentam 12 .…”
Section: Introductionunclassified
“…Current smokers and former smokObesity and smoking: CIPP modulators in SUI CIPP increases with BMI and that BMI is also an independent predictor for CIPP. Some studies have already shown the beneficial effects of weight loss on SUI (4,10,11). Nevertheless, one cannot predict the degree of improvement of SUI when treating obesity.…”
Section: Discussionmentioning
confidence: 99%